Method validation for determination of released cadmium and lead from paper for food contact materials - Waluvanarak, Jitwilai; Phonhong, Nootjarin; Buranakul, Warunrat; Luesaiwong, Wandee (Bulletin of Applied Sciences, 2022)
The method for determination of released cadmium and lead from paper for food contact by inductively coupled plasma optical emission spectrometry was validated according to EN 12498:2005 Paper and board-Paper and board intended to come into contact with foodstuffs-Determination of cadmium and lead in an aqueous extract. Results showed that instrument working range of cadmium and lead were 5-50 and 50-500 ug/L respectively. The limit of detection of cadmium and lead were 0.5 and 5.0 ug/L and the limit of quantitation of both elements were 5 and 50 ug/L. The bias and precision studies showed that percentage recovery and relative pooled standard deviation of both elements were 85.3-94.4 and 0.63-2.92 respectively. While measurement uncertainty was less than 15 % at 95 % confident limit of all elements.